TRADE OPENNESS AND LONG-TERM ECONOMIC GROWTH: EMPIRICAL EVIDENCE FROM UZBEKISTAN AND KAZAKHSTAN - Agzamov Boburxon Boistxonovich (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract. This article examines how trade openness relates to long-term economic growth in Uzbekistan and Kazakhstan, two landlocked economies that have pursued outward-oriented reforms in different sequences and at different speeds. Trade openness is commonly measured as the sum of exports and imports relative to GDP and is often viewed as a channel for productivity gains through competition, technology diffusion, and access to larger markets. Yet, openness can also transmit external shocks, deepen import dependence, and amplify commodity cycles— especially when institutions, logistics, and industrial upgrading lag behind. Using recent cross-country indicators and two country-focused empirical studies, the paper synthesizes the evidence on whether openness has supported growth in these economies and why results may differ across time horizons.